Antibiotic use in a district hospital in Kabul, Afghanistan: are we overprescribing? - Bajis, S. (Public Health Action, 2014)
Setting: A district hospital in Kabul, Afghanistan, supported by Médecins Sans Frontières (MSF). Objectives: To assess antibiotic prescribing practices in the out-patient department in summer (August 2013) and winter (January 2014). Design: Cross-sectional study, using routinely collected hospital data and using World Health Organization (WHO) defined daily dose (DDD) methodology. Results: An analysis of 4857 prescriptions (summer) and 4821 prescriptions (winter) showed that respectively 62% and 50% of all out-patients were prescribed at least one antibiotic. Prescriptions without a recorded diagnosis represented a sizeable proportion of all antibiotics prescribed. For upper respiratory tract infections (URTI), dental indications, urinary tract infections (UTI) and diarrhoea, good adherence to dosages recommended in the MSF standard treatment guidelines was observed when measured by DDD. However, certain drugs not indicated in the guidelines were prescribed, such as amoxicillin and metronidazole for UTI and azithromycin for URTI. Conclusion: Rates of antibiotic prescriptions for out-patients in a district hospital in Afghanistan were high, double the WHO recommendation of 30%. While systematic non-adherence to recommended dosages was not observed, inappropriate prescriptions for specific conditions may have occurred. This study suggests that knowledge about context-specific determinants of antibiotic prescribing is a first step towards promoting rational prescribing practices in such settings.